Analysis of Gen Z Consumer Behavior in Visiting Malaysian Crab Mangrove Tourist Destinations: The Role of Tourist Perceptions and Preferences - Elfitra Desy Surya; Sri Rahayu; Rashdan Bin Rashid; Muhammad Faishal Annas (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of tourist perception on loyalty mediated by tourist satisfaction in tourist destinations, focusing on Crab Mangrove Park, Malaysia. Tourists' perception of the quality of services, facilities, and natural attractions of destinations is considered an important factor in shaping the level of satisfaction which then affects tourist loyalty. In this study, we used a quantitative method with a survey approach to tourists who visited Crab Mangrove Park. The results of the study show that tourists' perception of tourist destinations has a positive and significant influence on their satisfaction. Traveler satisfaction, in turn, has been shown to mediate the relationship between perception and loyalty. Tourists who have a positive perception of the quality of service, natural beauty, and experience provided by the destination tend to feel satisfied and more loyal to the destination. This study advises tourist destination managers to improve the quality of services and experiences in accordance with travelers' preferences to create sustainable loyalty. Additionally, it's important for destination managers to pay attention to travelers' perceptions, as this contributes greatly to their satisfaction and loyalty levels in the future.